Augmentation of myocardial If dysregulates calcium homeostasis and causes adverse cardiac remodeling - Yampolsky, Pessah; Koenen, Michael; Mosqueira, Matias; Geschwill, Pascal; Nauck, Sebastian; Witzenberger, Monika; Seyler, Claudia; Fink, Thomas; Kruska, Mathieu; Bruehl, Claus; Schwoerer, Alexander Peter; Ehmke, Heimo; et al. (Nature Communications, 2019)
HCN channels underlie the depolarizing funny current (If) that contributes importantly to cardiac pacemaking. If is upregulated in failing and infarcted hearts, but its implication in disease mechanisms remained unresolved. We generated transgenic mice (HCN4tg/wt) to assess functional consequences of HCN4 overexpression-mediated If increase in cardiomyocytes to levels observed in human heart failure. HCN4tg/wt animals exhibit a dilated cardiomyopathy phenotype with increased cellular arrhythmogenicity but unchanged heart rate and conduction parameters. If augmentation induces a diastolic Na+ influx shifting the Na+/Ca2+ exchanger equilibrium towards ‘reverse mode’ leading to increased [Ca2+]i. Changed Ca2+ homeostasis results in significantly higher systolic [Ca2+]i transients and stimulates apoptosis. Pharmacological inhibition of If prevents the rise of [Ca2+]i and protects from ventricular remodeling. Here we report that augmented myocardial If alters intracellular Ca2+ homeostasis leading to structural cardiac changes and increased arrhythmogenicity. Inhibition of myocardial If per se may constitute a therapeutic mechanism to prevent cardiomyopathy.
Gesehen am 17.12.2024
Im Titel ist "f" bei "If" tiefgestellt